Climate Change, Cold Waves, Heat Waves, and Mortality: Evidence from a Lower Middle-Income Country - Cuong Viet Nguyen; Manh-Hung Nguyen; Toan Truong Nguyen (Global Labor Organization (GLO), 2022)
We estimate the impact of temperature extremes on mortality in Vietnam, using daily data on temperatures and monthly data on mortality during the 2000-2018 period. We find that both cold and heat waves cause higher mortality, particularly among older people. This effect on mortality tends to be smaller in provinces with higher rates of air-conditioning and emigration, and provinces with higher public spending on health. Finally, we estimate economic cost of cold and heat waves using a framework of willingness to pay to avoid deaths, then project the cost to the year 2100 under different Representative Concentration Pathway scenarios.
Keywords: I10; Q54; O15; R23; 330; climate change; weather extremes; mortality; health; Vietnam